The impact of religiosity on the disability, psychological well-being, and somatic health of multiple sclerosis patients. Issue 5 (28th May 2022) - Mohaghegh, Fahimeh; Eslami, Monireh; Dadfar, Mahboubeh; Lester, David; Ayten, Ali; Rashidizadeh, Amin; Shirzad, Fatemeh
ABSTRACT: The aim of the study was to predict disability, psychological wellbeing, and somatic health in multiple sclerosis (MS) patients with the mediating variable of religiosity. A sample of 128 patients was recruited, and were administered the Expanded Disability Status Scale, the World Health Organization-5 Well-Being Index, the Patient Health Questionnaire-15, and a Self-Rating Scale of Religiosity. Religiosity did not predict disability, psychological well-being, or somatic health. Religiosity was positively associated with MS duration and disability, but only in male patients. The predictors for predicting psychological wellbeing were age, disability, and somatic health. Patients with moderate/severe MS (EDSS >3) obtained higher mean scores on religiosity compared to patients with mild MS (EDSS ≤3) and, therefore, the severity of MS was a significant moderator between religiosity and psychological well-being. The findings suggest the importance of focusing on the type of religiosity, God representation, and attachment to God for clarifying the link between psychological well-being and religiosity among patients.